NOTARY RESPONSIBILITY IN CHECKING HALAL CAUSA REQUIREMENTS ON OBJECTS PROMISED - Dyah Ochtorina Susanti (Warmadewa Press, 2020)
This research is motivated by there is a case of cancellation (null and void) of an authentic deed made by a notary because it does not meet the halal causa requirements. This study aims to analyze and find the form of liability of the Notary in halal causa requirements on the promised object. The results of the study using the normative legal research with the statute approach, conceptual approach, and comparative approach. The results of this study showed that the form of legal liability of the Notary in examining halal causa requirements on the agreed object, namely using the type of liability based on fault, because if halal causa requirements are not fulfilled in the authentic deed which results in the deed being null and void, then it is mistakes of Notaries as officials who are authorized to make and be responsible. At the end of this study, the researcher also provided advice to the government to updated Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position by adding clauses related to the Notary's obligation to check the legal terms of the agreement; as well as advice to the Notary to be more careful, thorough, careful, not taking sides in checking halal causa requirements in the object of the agreement.